(untitled) (Orfeu, 2020)
Affirmative musical historiography, in essence shaped by musicology and folklore, has produced as non-existent the historical dimension of popular music, through the application of an objectual-personalistic epistemology based on a western-centered objectified conception of music. Although this is a zombie historiography, clearly outdated, it still inhabits the majority portion of the social imagery about music, especially present in undergraduate courses of music history. This paper problematizes this hegemonic conception, in order to achieve a (re) integration of practices from the popular subaltern world, that exists in the whole development of Western and especially Latin American history. This task will require a divergent framework through alternative concepts that can understand the peculiar features of musics in popular subaltern world: the localized, performative and dynamic attributes of musicking, through its nomadic, mestizo, transcultural and transmodern features.